Explaining Upper or Lower Extremity Crossover Effects of Visuomotor Choice Reaction Time Training. Issue 4 (August 2019) - Engeroff, Tobias; Giesche, Florian; Niederer, Daniel; Gerten, Sina; Wilke, Jan; Vogt, Lutz; Banzer, Winfried
Current evidence indicates a strong relation between improved visuomotor choice reaction time (VMRT) and a reduced risk of lower extremity injury, making both lower- and upper extremity VMRT training paradigms valuable to athletes. This investigation studied as yet unconfirmed crossover effects of upper extremity training on lower extremity performance; and we evaluated underlying relevant perceptual and cognitive adaptations. In this three-armed, randomized, controlled intervention, we used a computerized training device to compare participants receiving four weeks of upper ( n  = 12) and lower ( n  = 12) extremity VMRT training with a control group ( n  = 13) of healthy participants. Collectively, our participants had a mean age of 24.6 years ( SD  = 2.2), a mean height of 173 cm ( SD =  10), and a mean weight of 69.6 kg ( SD  = 12.1); 57% ( n  = 21) were female and 43% ( n  = 16) were male. We assessed participants' upper and lower extremity VMRT performance and domain-specific perceptual and cognitive abilities before and after intervention and analyzed differences between their before and after performances. Lower extremity training enhanced VMRT performances for both lower extremity and crossover upper extremity. Upper extremity training improved VMRT for upper extremity and increased cognitive choice reaction performance but yielded no crossover effects to lower extremity. We found no effects of VMRT training on other domain-specific cognitive performance markers (attention, executive function, memory, or working memory). VMRT training modulated only task-specific cognitive performance and induced crossover effects from lower extremity training to upper extremity performance but not vice versa.